Trihelix transcription factor GT-4 mediates salt tolerance via interaction with TEM2 in Arabidopsis - Wang, Xiao-Hong (BMC Plant Biol, 2014)
BACKGROUND: Trihelix transcription factor family is plant-specific and plays important roles in developmental processes. However, their function in abiotic stress response is largely unclear. RESULTS: We studied one member GT-4 from Arabidopsis in relation to salt stress response. GT-4 expression is induced by salt stress and GT-4 protein is localized in nucleus and cytoplasm. GT-4 acts as a transcriptional activator and its C-terminal end is the activation domain. The protein can bind to the cis-elements GT-3 box, GT-3b box and MRE4. GT-4 confers enhanced salt tolerance in Arabidopsis likely through direct binding to the promoter and activation of Cor15A, in addition to possible regulation of other relevant genes. The gt-4 mutant shows salt sensitivity. TEM2, a member of AP2/ERF family was identified to interact with GT-4 in yeast two-hybrid, BiFC and Co-IP assays. Loss-of-function of TEM2 exerts no significant difference on salt tolerance or Cor15A expression in Arabidopsis. However, double mutant gt-4/tem2 shows greater sensitivity to salt stress and lower transcript level of Cor15A than gt-4 single mutant. GT-4 plus TEM2 can synergistically increase the promoter activity of Cor15A. CONCLUSIONS: GT-4 interacts with TEM2 and then co-regulates the salt responsive gene Cor15A to improve salt stress tolerance. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-014-0339-7) contains supplementary material, which is available to authorized users.